Seismic Response of Flexibily-Connected Steel Frames - Harsoyo - (Unisia, 1992)
The response of typical low-rise steel building frames designed by the "Type 2 Consctruction" method to moderate earthquakes is examined. Such frames are often identified by large girders, small columns, and semi-rigid connections. The simple methods underlying the Type 2 design approach do not permit realistic consideration of the frame response to either static or dynamic loads. In this paper, typical flexibly connected Type 2 fiames will be analyzed for seismic resistance with the methods recommended by the 1988 Uniform Building Code. The results indicate that these Type 2 frame possess adequate strength, but may not have adequate lateral stiffness for moderate seismic loads